2018
DOI: 10.1109/tie.2018.2803756
|View full text |Cite
|
Sign up to set email alerts
|

An Energy Saving Variable Damping Seat Suspension System With Regeneration Capability

Abstract: In this paper, an energy saving variable damping seat suspension system is designed, manufactured and validated. A controllable electromagnetic damper (EMD), which consists of a permanent magnet synchronous motor (PMSM), a 3-phase rectifier, a metal-oxide-semiconductor field-effect transistor (MOSFET) switch module, an external resistor, a diode, and a capacitor, is designed and tested firstly. The EMD is integrated with a planetary gearbox to amplify its torque output, and both of them are installed on the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…us, an electrical circuit with an adjustable resistor is needed to achieve semiactively regulation of the damping force for such a device. As seen in Figure 3, Ning et al [24] suggested an approach based on the metal-oxide semiconductor field-effect transistor (MOSFET).…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…us, an electrical circuit with an adjustable resistor is needed to achieve semiactively regulation of the damping force for such a device. As seen in Figure 3, Ning et al [24] suggested an approach based on the metal-oxide semiconductor field-effect transistor (MOSFET).…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…It is difficult to reconstruct some projects which have been put into use. Literature [5][6][7][8] proposed the strategy of removing the AC filter of the DC sending-end bus during the fault and putting in a static, dynamic reactive power compensation device for reactive power compensation but did not consider the response time of the device and the impact of the moment of the fault on the wind farm. At present, the main dynamic reactive power compensation devices in the power grid are SVC, static var generator (SVG), and synchronous condenser.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent studies, various approaches were proposed to improve the ride comfort and avert the fatigue risks associated to the human body. Some researchers have improved the vehicle suspension system to reduce the input vibration into the human body [10][11][12], while others focus on enhancing the vehicle seat suspension design [13]. Similarly, few studies integrated both the vehicle suspension system and seat suspension system to isolate vibration transmitted to human body [14,15].…”
Section: Introductionmentioning
confidence: 99%